A proposal for a dipole-generated BLUF domain mechanism - Mathes, Tilo; Götze, Jan P. (Frontiers in Molecular Biosciences, 2015)
The resting and signaling structures of the blue-light sensing using flavin (BLUF) photoreceptor domains are still controversially debated due to differences in the molecular models obtained by crystal and NMR structures. Photocycles for the given preferred structural framework have been established, but a unifying picture combining experiment and theory remains elusive. We summarize present work on the AppA BLUF domain from both experiment and theory. We focus on IR and UV/vis spectra, and to what extent theory was able to reproduce experimental data and predict the structural changes upon formation of the signaling state. We find that the experimental observables can be theoretically reproduced employing any structural model, as long as the orientation of the signaling essential Gln63 and its tautomer state are a choice of the modeler. We also observe that few approaches are comparative, e.g. by considering all structures in the same context. Based on recent experimental findings and a few basic calculations, we suggest the possibility for a BLUF activation mechanism that only relies on electron transfer and its effect on the local electrostatics, not requiring an associated proton transfer. In this regard, we investigate the impact of dispersion correction on the interaction energies arising from weakly bound amino acids.